2019
DOI: 10.3386/w25470
|View full text |Cite
|
Sign up to set email alerts
|

How Prevalent Is Downward Rigidity in Nominal Wages? Evidence from Payroll Records in Washington State

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 15 publications
4
27
0
Order By: Relevance
“…12 The longer sample is crucial to document large time variations in the wage change distribution since the Great Recession and to test for allocative consequences of DNWR. Another paper that has recently started using Washington data is Jardim et al (2018). 13 Their analysis confirms our basic results on the wage change distribution, which is useful given the confidential nature of the LEHD data.…”
Section: Introductionsupporting
confidence: 57%
“…12 The longer sample is crucial to document large time variations in the wage change distribution since the Great Recession and to test for allocative consequences of DNWR. Another paper that has recently started using Washington data is Jardim et al (2018). 13 Their analysis confirms our basic results on the wage change distribution, which is useful given the confidential nature of the LEHD data.…”
Section: Introductionsupporting
confidence: 57%
“…Two research teams - Kurmann and McEntarfer (2017) and Jardim, Solon, and Vigdor (2018) -have used the Washington data to study job stayers' year-to-year changes in quarterly average hourly earnings, and both have obtained results similar to those in the British studies.…”
Section: United Statesmentioning
confidence: 85%
“…Wage rigidities are often used to explain this mild response of wage growth to tight labor market conditions, depicted as a flattening of the wage Phillips curve (see Daly and Hobijn (2014)). However, recent empirical evidence has shown that downward nominal wage rigidities are not as binding as we initially thought (see Jardim et al (2019) and Elsby and Solon (2018)).…”
Section: Introductionmentioning
confidence: 74%